KARAKTERISASI PARTIKEL PRA-KARBON DARI BUNGA RUMPUT GAJAH (PENNISETUM POLYSTACHYON) DENGAN CAMPURAN SURFAKTAN ANIONIK SODIUM DODESIL SULFAT SEBAGAI BAHAN DASAR SUPERKAPASITOR - E. Taer; H. Halim; R. Farma; R. Taslim (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
A research on the manufacture of pre-carbonized particles (PCP) in nano-meter size from elephant grass flower has been studied. The process of making (PCP) using a combination of ballmilling methods and the addition of the anionic surfactant sodium dodecyl sulfate and followed by chemical activation using KOH. Pre-carbonization processes carried out at a temperature of 280 Â°C and then followed by milling and sieving process to obtain the particle size smaller than 38 Î¼m. The next stages of the sample (PCP) is mixed with a two concentrations of surfactant are 0.5 M and 1.5 M. The final stages to produce the (PCP) using a process of ballmilling with milling time of 80 hours and was closed by chemical activation using KOH activator with a concentration of 0.7 M. Scanning Electron Microscope (SEM) images showed the (PCP) in the particle size range of 100 - 200 nm. Analysis with energy dispersiv X-rays showed the carbon contentin in the sample of 52%. Results of X-ray data diffraction found that the carbon peak at 2Î¸ angles, namely 26,2690 and 45,3470 that describes the elements carbon with a crystal orientation (002) and (100). Keywords:Elephant Grass, surfactants, Ballmilling, Partikel Pre-carbon.